2015
DOI: 10.1007/s12311-015-0646-z
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Factors and Cellular Mechanisms Involved in the Survival of Cerebellar Granule Neurons

Abstract: Cerebellar granule neurons (CGNs) constitute the most abundant neuronal population in the mammalian brain. Their postnatal generation and the feasibility to induce their apoptotic death in vitro make them an excellent model to study the effect of several neurotransmitters and neurotrophins. Here, we first review which factors are involved in the generation and proliferation of CGNs in the external granule layer (EGL) and in the regulation of their differentiation and migration to internal granule layer (IGL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…More specifically, we found that genes associated with the two major glutamate receptors, the N-methyl-D-aspartic acid (NMDA) receptors and the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, were highly enriched in the pathway analysis ( Fig 6B ). NMDA receptors were reported to be essential for the maturation and survival of CGCs [ 44 , 45 ]. We confirmed that the m 6 A-modified exons ( S8B and S8C Fig ) in these synapse-associated genes, such as Grin1 , Atp2b3 , Grm1 , and Lrp8 , were excluded in cKO cerebellums by RT-PCR ( Fig 6C and S9C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, we found that genes associated with the two major glutamate receptors, the N-methyl-D-aspartic acid (NMDA) receptors and the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, were highly enriched in the pathway analysis ( Fig 6B ). NMDA receptors were reported to be essential for the maturation and survival of CGCs [ 44 , 45 ]. We confirmed that the m 6 A-modified exons ( S8B and S8C Fig ) in these synapse-associated genes, such as Grin1 , Atp2b3 , Grm1 , and Lrp8 , were excluded in cKO cerebellums by RT-PCR ( Fig 6C and S9C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, primary CGNs that well express NMDA receptors are widely used in the field of neuroscience and neuropharmacology ( Contestabile, 2002 ; Xifro and Rodriguez-Alvarez, 2015 ). These cells are popular because it is easy, in vitro , to acquire abundant and homogeneous CGNs (over 95% are CGNs in the cerebellum) from the explanted cerebellum than other neurons (hippocampal and cortical neurons).…”
Section: Introductionmentioning
confidence: 99%